Spatiotemporal variation and driving forces of soil salinization in the lower reach of arid endorheic basins: Critical role of lake system and groundwater overflow - Yong Xiao; Wenxu Hu; Yuqing Zhang; Zhen Zhao; Guangxiong Qin; Huijuan Chen; Liwei Wang; Shaokang Yang; Jie Wang; Qiuming Pei; Yu Liu (Agricultural Water Management)
Arid endorheic basins confront the most severe soil salinization challenge globally, particularly in their lower reaches. This research focuses on the spatiotemporal dynamics and underlying mechanism of soil salinization in the lower reaches of arid endorheic basin. The arid endorheic Bayin River watershed on Qinghai-Xizang Plateau was investigated with the aid of an integrated approach combining remote sensing analysis, Geodetector technique, visual interpretation, and field surveys. Results show that the lower reach exhibits significant spatial heterogeneity and temporal variation in soil salinization. Terrain elevation is the primary and most influential natural factors governing the spatial pattern of soil salinization in the arid endorheic lower reach, followed by climate and groundwater factors. Soil salinity variations along elevation in the eastern and western study area are unexpected and discrepant, driven by contrasting hydrodynamic influences of the salt terminal lake Gahai and the freshwater through-flow lake Hurleg. Human activity (land use) is the most influential driver of soil salinization across the study area, exhibiting a fluctuating and increasing trend, yet it is constrained by natural forces, particularly precipitation-induced groundwater overflow floods. Despite expanding human activities, the combined effects of individual natural factors on soil salinization remain negligible. A conceptual model was established to elucidate the mechanisms controlling and driving soil salinization patterns in the lower reach of arid endorheic basins, with emphasis on the hydrodynamic effects of groundwater overflow and terminal and through-flow lakes. This research provides new insights into the formation mechanisms and remediation strategies for soil salinization in arid endorheic basins.